Phosphorylated OmpR Is Required for Type 3 Fimbriae Expression in Klebsiella pneumoniae Under Hypertonic Conditions - Lin, Tien-Huang; Chen, Yeh; Kuo, Jong-Tar; Lai, Yi-Chyi; Wu, Chien-Chen; Huang, Chun-Fa; Lin, Ching-Ting (Frontiers in Microbiology, 2018)
OmpR/EnvZ is a two-component system that senses osmotic signals and controls downstream gene expression in many species of Enterobacteriaceae. However, the role of OmpR/EnvZ in Klebsiella pneumoniae remains unknown. In this study, we found that production of MrkA, the major subunit of type 3 fimbriae, was decreased under hypertonic conditions. A deletion mutant of ompR and a site-directed mutant with a single amino acid substitution of aspartate 55 to alanine (D55A), which mimics the unphosphorylated form of OmpR, markedly reduced MrkA production under hypertonic conditions. These results indicate that K. pneumoniae type 3 fimbriae expression is activated by the phosphorylated form of OmpR (OmpR P). Although no typical OmpR P binding site was found in the PmrkA sequence, mrkA mRNA levels and PmrkA activity were decreased in the ompR and ompRD55A strains compared with the wild type strain, indicating that OmpR P mediates type 3 fimbriae expression at the transcriptional level. Previous reports have demonstrated that a cyclic-di-GMP (c-di-GMP) related gene cluster, mrkHIJ, regulates the expression of type 3 fimbriae. We found that both the ompR and ompRD55A mutants exhibited decreased mrkHIJ mRNA levels, intracellular c-di-GMP concentration, and bacterial biofilm amount, but increased total intracellular phosphodiesterase activity in response to hypertonic conditions. These results indicate that OmpR P regulates type 3 fimbriae expression to influence K. pneumoniae biofilm formation via MrkHIJ and modulation of intracellular c-di-GMP levels. Taken together, we herein provide evidence that OmpR P acts as a critical factor in the regulation of the c-di-GMP signaling pathway, type 3 fimbriae expression, and biofilm amount in K. pneumoniae in response to osmotic stresses.